Factors associated with repeat diagnosis of syphilis in genitourinary medicine (GUM) clinic attendees in the North East of England, 2002–2014. (July 2018) - Dolan, G; Chauhan, M; Foster, K; Basta, M; Bushby, S; White, C; Verlander, NQ; Gorton, R
This study aimed to identify factors associated with repeat syphilis infection in North East England, in order to inform local prevention and control opportunities. We undertook a case–case study comparing individuals diagnosed with single or multiple episodes of syphilis infection within genitourinary medicine (GUM) clinics in NE England (12 clinics serving a population of 2.5 million). Study cases were verified as having had true re-infection by a GUM clinician (using serological and/or clinical parameters) and control cases (3 per case) frequency matched to cases by age and year of presentation. The odds of exposure to sexual behavioural and clinical factors were compared for cases and control cases using stepwise multivariable logistic regression. We included 66 cases and 235 control cases. The majority of cases (62/66) and control cases (165/235) were men who had sex with men (MSM). Data were missing for 0–64% of cases across different variables. Following multivariable analysis HIV seropositivity (OR 23.3, 95% CI 4.32–125.9), failure to attend follow-up (OR 4.63, 95% CI 1.11–19.31), stage of infection and deprivation were associated with re-infection ( p < 0.001). In this study, HIV seropositivity and failure to attend follow-up were associated with re-infection with syphilis. Actions targeted at these groups may help to reduce ongoing transmission.